Overview of Unilateral and Bilateral Pediatric Facial Paralysis: Workup, Treatment, and Frontiers - Wiebe, Jordan E.; Mulenga, Chilando; Crabtree, Jordan R.; Hussain, Arif; Borschel, Gregory H. (Facial Plastic Surgery, 2024)
Pediatric facial nerve paralysis can present significant challenges based on its various etiologies, unique approach to treatment options, and overall outcomes. It can impact both the child and parent when regarding function, appearance, and psychosocial implications. The etiology of facial nerve palsy can include congenital, traumatic, iatrogenic, and idiopathic causes. In some, the paralysis is transient while others have permanent loss of function. A thorough evaluation and differential diagnosis are essential to guide treatment planning. The purpose of this paper is to review facial paralysis in children with a focus on surgical management.
Keywords: facial palsy; facial paralysis; facial reanimation; cross facial nerve graft; Moebius Syndrome